KRISIS EKOLOGI DALAM NOVEL TERUSLAH BODOH JANGAN PINTAR KARYA TERE LIYE: KAJIAN EKOKRITIK GREG GARRARD - Lisa Firnanda; Ridlwan Ridlwan; Suher Suher (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2025)
The relationship between humans and nature has been an important topic in many fields. Man's view of nature has changed throughout History, from a more harmonious view with nature to a more exploitative view. Human activities have caused environmental damage and loss of biodiversity. The focus of this research is the ecological crisis that occurs in the novel Teruslah Bodoh Jangan Pintar by Tere Liye based on Greg Garrard's concept of ecocriticism. The purpose of this research is to describe the ecological crisis that occurs in the novel Teruslah Bodoh Jangan Pintar by Tere Liye based on Greg Garrard's concept of ecocriticism. This research method is descriptive qualitative. The research data source is the novel Teruslah Bodoh Jangan Pintar by Tere Liye. The results showed that there are several forms of ecological crisis that occur, namely: deforestation, ecosystem pollution, floods and droughts, land reduction, natural explotation, and the extinction of endemic animals.